THE IMPACT OF SECONDARY SKIN ON NATURAL LIGHTING IN THE OFFICE OF BPS SALATIGA: A SIMULATION STUDY USING DIALUX EVO 13.0 AND GREEN ARCHITECTURE PRINCIPLES - Meutia, Naila; Lesmana, Fadhiila Aulia; Widiastuti, Ratih; Bramiana, Chely Novia (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2025)
The development of technology and the demand for sustainability encourage the importance of applying green architecture principles in office buildings. The implementation of green architecture principles in government office buildings often encounters challenges such as limited stakeholder awareness, budget constraints, and the absence of passive design strategies that optimize natural resources. These conditions highlight the urgency of exploring design interventions that balance energy efficiency, user comfort, and sustainability. This study aims to evaluate the effectiveness of using secondary skin in improving daylighting in the Central Statistics Agency (BPS) of Salatiga City. The approach used is a green architecture approach with a focus on energy efficiency and the visual comfort of space users. The research method includes analyzing the existing conditions and redesigning the facade using secondary skin elements based on daylighting simulation through DIALux Evo, Revit, and EDGE App software. Simulations were conducted on several main workspaces to compare the value of light intensity between the existing conditions and the redesign results. A comparative simulation between DIALux Evo 13.0 and Autodesk Revit revealed consistent daylight distribution patterns, confirming the effectiveness of a 90° vertical secondary skin configuration. The EDGE Application 2.1.5 analysis indicated potential energy savings of 55.32% in redesigned conditions, highlighting the secondary skin's role in reducing artificial lighting dependency and contributing to the overall building's energy efficiency. The results show that the application of secondary skin can improve the even distribution of natural light and reduce dependence on artificial lighting. In addition, the proposed redesign contributes to achieving energy efficiency principles and improving workspace quality. This research is expected to serve as a reference for the application of sustainable passive design in government agency buildings in tropical areas.